58.4k views
5 votes
FOR 20 POINTS! GIVE REAL ANSWERS PLEASE. THANKS!

Davon's solution to the equation -2(x - 5) + 3 = -4 is shown below.
-2(x - 5) + 3 = -4

Step 1 -2x - 5 + 3= -4
Step 2 -2x - 2 = -4
Step 3 -2x = -2
Step 4 x = -1

In which step did the first mistake occur?

Step 1

Step 4

Step 2

Step 3

User WEFX
by
5.8k points

1 Answer

3 votes

Answer:

8.5

Explanation:

-2(x-5)+3=-4

Step 1 distribute

−2+10+3=−4

Step 2 add the numbers

-2x+13=-4

Step 3 subtract 13 from both sides of the equation

−2-13+13=-4-13

Step 4 get ride of the two 13

-2x=-4-13

Step 5 subtract -4 subtract 13

-2x=-17

Step 6 divide -17 by -2

-2x/-17

Step 6 answer

8.5

User Roger Dodger
by
6.2k points